Speaking to the Ghost: An autoethnographic journey with Elwyn. Issue 7 (6th June 2016) - Heyward, Paul; Fitzpatrick, Esther
Abstract: As educators we are haunted. This haunting takes place on several levels, through our personal histories, through key theoretical ideas we have encountered on our journeys, and by those significant educators who have gone before. This paper highlights how Elwyn S. Richardson continues to haunt education in New Zealand. Also how Elwyn, in turn, was haunted by 'Wal' and John Dewey. Rubbing up against neo-liberal reform, philosophers such as Elwyn, give us permission to develop our own personal educational philosophy. Through employing an arts-based autoethnography, we explore how our educational journeys have been haunted by Elwyn. And by drawing on Jacques Derrida's directive, 'speak to the ghost', we summon up Elwyn. To do this we write a series of fictional letters which enable us to reflect on one author's memories. Through analysis of these letters we demonstrate the importance of the Arts as a method to critically reflect upon, and rise above, the dominant neo-liberal ideology we work within. We speculate here that a strong personal philosophy has the potential to disrupt and engage educators critically with an institutional philosophy that continues to dominate much of mainstream education in New Zealand.